2021
DOI: 10.1109/lca.2021.3109945
|View full text |Cite
|
Sign up to set email alerts
|

BTB-X: A Storage-Effective BTB Organization

Abstract: Many contemporary applications feature multi-megabyte instruction footprints that overwhelm the capacity of branch target buffers (BTB) and instruction caches (L1-I), causing frequent front-end stalls that inevitably hurt performance. BTB is crucial for performance as it enables the front-end to accurately resolve the upcoming execution path and steer instruction fetch appropriately. Moreover, it also enables highly effective fetch-directed instruction prefetching that can eliminate many L1-I misses. For these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Using these traces, we characterize BTB replacement challenges to design Thermometer, a novel profileguided BTB replacement technique. We validate Thermometer's effectiveness on 13 data center applications and on CBP-5 [15] and IPC-1 [17] traces that prior work [20,24,57,58] evaluate their frontend optimizations.…”
Section: Experimental Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Using these traces, we characterize BTB replacement challenges to design Thermometer, a novel profileguided BTB replacement technique. We validate Thermometer's effectiveness on 13 data center applications and on CBP-5 [15] and IPC-1 [17] traces that prior work [20,24,57,58] evaluate their frontend optimizations.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…We profile only a portion of each application's execution; this portion is different from the tested execution and uses different inputs. Apart from evaluating Thermometer on these 13 real-world applications, we also evaluate Thermometer on a wide-range of common traces (663 CBP-5 [15] traces and 50 IPC-1 [17] traces) like prior work [20,24,57,58].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to BTB prefetching, researchers have investigated BTB entry organizations to maximize the number of entries in a given storage budget [14,37,38].…”
Section: Related Workmentioning
confidence: 99%
“…For example, certain BTB structures allocate different-sized target table entries to accommodate more branch instructions [8]. Asheim's experiments demonstrated that gradually expanding the BTB structure can significantly reduce mispredictions [9]. However, the increased BTB capacity introduces more access latency, resulting in longer branch instruction prediction times and increase power consumption.…”
Section: Introductionmentioning
confidence: 99%